A revision and key for the tribe Diaphorolepidini (Serpentes: Dipsadidae) and checklist for the genus Synophis - Pyron, Alexander (2016)
The genus Synophis contains a number of enigmatic species, distributed primarily in the Andean highlands of northern South America. Their extreme crypsis and rarity has precluded detailed study of most species. A recent flurry of collection activity resulted in the accession of many new specimens, and the description of 4 new species in 2015, doubling the num-ber of described taxa. However, lingering questions remain regarding the assignment of many new and historical speci-mens, the morphological limits and geographical ranges of the species, and their phylogenetic relationships. We analyze new and existing morphological and molecular data to produce a new molecular phylogeny and revised morphological descriptions. We validate the previously unavailable tribe name Diaphorolepidini Jenner, Pyron, Arteaga, Echevarría, & Torres-Carvajal tribe nov., describe a 9th species Synophis niceforomariae Pyron, Arteaga, Echevarría, & Torres-Carvajal sp. nov., and offer new Standard Names in English and Spanish for the group: Andean Shadow Snakes and Culebras An-dinas de la Sombra, respectively. A variety of features such as vertebrae and hemipenes show an interesting range of vari-ation in the group, which should be evaluated in future studies, to refine species limits and diagnoses further. Cryptic and undiscovered diversity undoubtedly remains, and we hope this summary provides a robust basis for future work. © Copyright 2016 Magnolia Press.